Research on restenosis characteristics and related factors in patients after coronary artery intervention with drug-eluting stents - Binh, Ho Anh; Lam, Nguyen Viet (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Objectives: To evaluate the characteristics of in-stent restenosis (ISR) and its associated risk factors in patients undergoing percutaneous coronary intervention (PCI) with drug-eluting stents (DES), and to assess their clinical implications. Methods: This cross-sectional descriptive study included 70 patients who had undergone PCI with DES and were diagnosed with ISR within two years post-intervention at the Cardiovascular Center, Hue Central Hospital, from March 2021 to August 2023. Data were collected on demographic characteristics, cardiovascular risk factors, lesion properties, and restenosis severity. Multivariate logistic regression was performed to identify independent risk factors for ISR. Results: The 70 patients in the study had an average age of 70.43 ± 8.99 years, 67.14% were male. Restenosis of the anterior interventricular artery accounted for the highest rate of about 61.4%. The rate of strict restenosis (≥70%) accounted for 67.1% in the 2 groups. The average length of stenosis was 16.73 ± 10.48 mm. The length of the lesion in the DES 1 group (14.04 ± 5.78 mm) was shorter than that in the DES 2 group (20.77 ± 14.22 mm) with p < 0.05 and the DES 2 group had a more localized stenosis than the DES 1 group with p < 0.05. Key risk factors for ISR included diabetes, renal failure, and dyslipidemia. Additionally, post-interventional vessel diameter, lesion length, and the use of first-generation DES were significantly associated with diffuse ISR (p < 0.05). Conclusion: ISR remains a major challenge in PCI with DES. It is influenced by lesion characteristics, patient comorbidities, and stent generation. Further prospective studies are required to confirm these findings and develop targeted prevention strategies.